Classroom instruction that works - Cornwell, Ken; Association for Supervision and Curriculum Development (Alexandria, Va. : ASCD, 2012)
The'Class instruction that works' book comes to life in this engaging new production focused on its use in elementary school, [middle school, or high school]. Join Ceri Dean, coauthor of'Classroom instruction that works,' and a group of elementary, [middle, or high school,] educators as they leverage elements from the'Classroom instruction that works' framework to transform their practice and their communities.
[V.1] Elementary school (50 min.) -- [v.2] Middle school (50 min.) -- [v.3] High school (50 min.)
ASCD Executive director, Gene R. Carter ; interim chief program development officer, Ed Milliken ; director of content, David Hargis ; executive producer, multimedia, Cary Goldweber ; managing director, creative services, Gary Bloom.
DVD format
Keywords: Effective teaching -- United States; Learning -- Handbooks, manuals, etc; Academic achievement -- Handbooks, manuals, etc; Academic achievement -- United States; Classroom management -- United States